Case Series Zinner Syndrome: A Series Depicting Rare Anomaly of the Male Genitourinary Tract. - Dr Ayesha Naaz, Dr Mudasir Hamid Bhat , Dr Irfan Robbani, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Zinner syndrome is a developmental amalgamation, characterized by the presence of threecongenital anomalies: unilateral seminal vesicle cyst, ejaculatory duct blockage and unilateral